IbBBX24 Promotes the Jasmonic Acid Pathway and Enhances Fusarium Wilt Resistance in Sweet Potato - Zhang, Huan (Plant Cell, 2020)
Cultivated sweet potato (Ipomoea batatas) is an important source of food for both humans and domesticated animals. Here, we show that the B-box (BBX) family transcription factor IbBBX24 regulates the jasmonic acid (JA) pathway in sweet potato. When IbBBX24 was overexpressed in sweet potato, JA accumulation increased, whereas silencing this gene decreased JA levels. RNA sequencing analysis revealed that IbBBX24 modulates the expression of genes involved in the JA pathway. IbBBX24 regulates JA responses by antagonizing the JA signaling repressor IbJAZ10, which relieves IbJAZ10’s repression of IbMYC2, a JA signaling activator. IbBBX24 binds to the IbJAZ10 promoter and activates its transcription, whereas it represses the transcription of IbMYC2. The interaction between IbBBX24 and IbJAZ10 interferes with IbJAZ10’s repression of IbMYC2, thereby promoting the transcriptional activity of IbMYC2. Overexpressing IbBBX24 significantly increased Fusarium wilt disease resistance, suggesting that JA responses play a crucial role in regulating Fusarium wilt resistance in sweet potato. Finally, overexpressing IbBBX24 led to increased yields in sweet potato. Together, our findings indicate that IbBBX24 plays a pivotal role in regulating JA biosynthesis and signaling and increasing Fusarium wilt resistance and yield in sweet potato, thus providing a candidate gene for developing elite crop varieties with enhanced pathogen resistance but without yield penalty.